The relationship between corporate social responsibility and corporate financial performance: the moderating role of corporate reputation - Wang, Chun (2022)
Corporate social responsibility (CSR) and sustainable development have become more widely understood in recent years, requiring companies to abandon their sole goal of maximising shareholder value and re-examine their stakeholder relationships. CSR has gradually become an important factor that firms cannot overlook for businesses to gain a competitive advantage in the future. However, scholars hold varying opinions about the relationship between CSR and corporate financial performance (CFP), with evidence supporting positive, negative, and even no correlation. Furthermore, some scholars believe that there are other factors that moderate the relationship between CSR and CFP. This paper argues that, in the short term, a company's CSR activities help improve its corporate reputation and gain stakeholder support, thereby enhancing CFP. However, the company's practice of CSR incurs a substantial cost that is difficult for companies to afford over a long period of time. In particular, inconsistency between the company's strategic goals and CSR activities is more likely to cause financial losses. A company that wishes to gain a long-term competitive advantage through CSR activities should align them with the company's strategic goals. This paper explores the relationship between CSR and CFP and examines the moderating role of corporate reputation on that relationship. Based on the correlation and regression analysis of the data of 731 Chinese listed companies from 2011 to 2019, this paper verifies the proposed research hypothesis and draws the following two conclusions: 1) CSR and CFP are significantly correlated, with short-term financial performance reflecting significant positive correlation and significant negative correlation from the perspective of long-term financial performance; 2) Corporate reputation weakens the impact of CSR on CFP.